E. coli infection disrupts the epithelial barrier and activates intrinsic neurosecretory reflexes in the pig colon - Traserra, Sara; Casabella-Ramón, Sergi; Vergara, Patri; Jimenez, Marcel (Frontiers in Physiology, 2023)
This study aims to assess the barrier integrity and possible activation of enteric neural pathways associated with secretion and motility in the pig colon induced by an enterotoxigenic Escherichia coli (ETEC) challenge. 50 Danbred male piglets were used for this study. 16 were challenged with an oral dose of the ETEC strain F4+ 1.5 x 109 colony-forming unit. Colonic samples were studied 4- and 9-days post-challenge using both a muscle bath and Ussing chamber. Colonic mast cells were stained with methylene blue. In control animals, electrical field stimulation induced neurosecretory responses that were abolished by tetrodotoxin (10-6M) and reduced by the combination of atropine (10-4M) and α-chymotrypsin (10U/mL). Exogenous addition of carbachol, vasoactive intestinal peptide, forskolin, 5-HT, nicotine, and histamine produced epithelial Cl- secretion. At day 4 post-challenge, ETEC increased the colonic permeability. The basal electrogenic ion transport remained increased until day 9 post-challenge and was decreased by tetrodotoxin (10-6M), atropine (10-4M), hexamethonium (10-5M), and ondansetron (10-5M). In the muscle, electrical field stimulation produced frequency-dependent contractile responses that were abolished with tetrodotoxin (10-6M) and atropine (10-6M). Electrical field stimulation and carbachol responses were not altered in ETEC animals in comparison with control animals at day 9 post-challenge. An increase in mast cells, stained with methylene blue, was observed in the mucosa and submucosa but not in the muscle layer of ETEC-infected animals on day 9 post-challenge. ETEC increased the response of intrinsic secretory reflexes and produced an impairment of the colonic barrier that was restored on day 9 post-challenge but did not modify neuromuscular function.